2018
DOI: 10.4236/acs.2018.82015
|View full text |Cite
|
Sign up to set email alerts
|

Further Laboratory Experiments on Aerosol Scavenging in Mixed Clouds to Assess the Role of Phoretic Forces and Particle Solubility

Abstract: Scavenging experiments have been performed in a cloud chamber inside a cold room with different aerosol particles: Paraffin particles, NaCl particles, Magnesium oxide particles, Carbon particles, Sahara dust particles. Essentially the experimental tests were carried on following the sequence of operations: the generation of the aerosol particles, their injection in the lower part of the cloud chamber, injection of water droplets in the whole chamber volume, nucleation of ice crystals, collection of ice crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In the field of atmospheric science, researchers began to study the transport mechanism of Stefan flow when exploring the interaction of raindrops or ice crystals with aerosol particles. Vittori, 46 Hallet and Oraltay, 47 Oraltay and Hallet, 48 and Prodi et al 49 investigated by experiment the mechanism of aerosol particle collection in the mixed cloud where evaporating droplets and growing ice crystals coexist. The research results showed that the presence of supercooled droplets in the mixed cloud can effectively improve the collection efficiency of submicrometer particles on the surface of ice crystals.…”
Section: Overview Of Experimental Work On Particle Collection Involvi...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of atmospheric science, researchers began to study the transport mechanism of Stefan flow when exploring the interaction of raindrops or ice crystals with aerosol particles. Vittori, 46 Hallet and Oraltay, 47 Oraltay and Hallet, 48 and Prodi et al 49 investigated by experiment the mechanism of aerosol particle collection in the mixed cloud where evaporating droplets and growing ice crystals coexist. The research results showed that the presence of supercooled droplets in the mixed cloud can effectively improve the collection efficiency of submicrometer particles on the surface of ice crystals.…”
Section: Overview Of Experimental Work On Particle Collection Involvi...mentioning
confidence: 99%
“…The experimental studies in section show that the Stefan flow prevails over other particle transport mechanisms and pushes particles away from the evaporating surface. ,, Meanwhile, the calculation results show that the phoretic force caused by evaporation can significantly enhance the deposition of submicrometer particles in the range of 0.01–1 μm particle size on the evaporating surface in most theoretical studies. Therefore, the particle collection efficiency by theoretical calculation is much higher than the experimental results. , , ,,,,, We suggest that the inconsistency between the theoretical calculation and the experimental results originates from the defects of the models.…”
Section: Overview Of Theoretical Work On Particle Collection Involvin...mentioning
confidence: 99%